Nutritional interventions in obese and malnutrided children (Research, Society and Development, 2019)
This paper aims to survey intervention studies aimed at children with low weight / malnutrition and overweight / obesity. This is an integrative review, performed in December 2018. It was performed in six steps: definition of the guiding question; selection of scientific articles to be reviewed, categorization and evaluation of these studies. The results show the importance of a food distribution program for malnourished children, and physical exercise and nutritional guidance for obese children. As well as multidisciplinary intervention programs involving children and families. It is concluded that nutritional interventions are of fundamental importance for the prevention and / or treatment of food deficiencies or excesses.